A Compact Antenna with WiMAX and WLAN bands notched for UWB applications - V.Prashanth, K; Umamaheswari, Bonthu; Akhil, G; Vamsi krishna, G; Venkata Sai chandu, M (International Journal of Engineering and Technology, 2018)
A Compact antenna with WiMAX and WLAN bands notched for ultra wide band (UWB) applications is proposed. The proposed antenna is designed for the planar ultra wide band (UWB) antenna and ultra wide band (UWB) antenna having two band rejections. The proposed antenna overall size is 30mm x 40mm x 1.6mm. The antenna consists of a rectangular patch on the top of FR4 substrate with 50ohm feed with defected ground structure. This patch consists of one round cut at each corner having radius 1.575mm. The simulated band width with return loss (RL) >=10db is 3.1 to 11.2 GHz with VSWR<2. It works for the applications of WiMAX system at 3.5GHz (3.3 â€“ 3.7 GHz), C-band satellite communication (3.7 - 4.2 GHz), wireless local area network (WLAN) system at 5GHz (5.15 â€“ 5.825 GHz), X-band satellite communication system (7.25 - 7.75 GHz). The ultra wide band frequency range for these wireless systems causes interference. To diminish obstruction, the band rejection is made. WiMAX and WLAN groups are dismissed by designing slots on the patch. This antenna has an incredible pick up in the Gain while a sharp drop in the rejected groups.Â